A Pragmatic Study of Hate Speech in Some American Animated Movies - Fadhel, Asawer; Sahib Mehdi Muhammed , Wafaa (Journal of College of Education, 2023)
Language can be used to express positive thoughts and reflect positive perceptions of others. Language, on the other hand, might do the opposite. Hate speech is the language directed at a particular group of people. It incites hostility, violence, or discrimination against others based on a difference in race, religion, or gender, among others. People have become more interested in hate speech due to its impact on individuals and societies. It is argued that hate speech is common in American animated movies that are produced for the young and children. This renders such a phenomenon more dangerous. This study aims to answer the following questions: What are the motivations that incite hate speech in three different American animated movies? What are the pragmatic strategies used to convey it in the data under scrutiny? Which of these pragmatic strategies are the most prevalent? And has hate speech changed in terms of its motivations and pragmatic manifestation through time? This study develops an analytical framework be the basic apparatus for analyzing the data. This study uses Searle's theory (1975) and Culpeper's (1996, 2015) impoliteness. Three American animated movies from three different periods have been chosen: Cinderella (1950), Pocahontas (1995), and Zootopia (2016). The findings of this study have led to some conclusions. The most basic one is that each movie employs the same pragmatic strategies to convey hate speech, but its motivations are different.
Keywords: Keywords: Animated movies, hate speech (henceforth HS), impoliteness, pragmatics, speech acts (henceforth SAs).